Radiation Therapy for Extranodal Lymphomas - Sasai, Keisuke; Oguchi, Masahiko; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This book is devoted to sharing the knowledge and experience of expert radiation therapy (RT) for extranodal lymphomas. For that purpose, the authors provide clinical-pathological information, precise RT techniques, and treatment results, i.e., disease control and survival, of all extranodal lymphomas. Over the past 10 years, specific techniques have been updated, from 3-dimensional conformal RT to intensity modulated RT / volumetric-modulated arc therapy. Precise targeting such as image-guided RT and active breathing control are now capable of treating lymphoma lesions that shift with respiration or peristalsis. This book, serving as a guide, provides the necessary knowledge for radiation oncology, practice, and planning involving the RT techniques of treating extranodal lymphomas. In addition, it equips oncologists, hematologists, and medical oncologists to refer patients with extranodal lymphomas to radiation oncologists for appropriate treatment in a timely manner. Therefore this volume will greatly benefit all oncologists, including radiation and medical oncologists, as well as hematologists.
1 Primary Central Nervous System Lymphomas -- 2 Ocular Adnexal Lymphoma -- 3 Extranodal NK/T Cell lymphoma, Nasal Type -- 4 Thyroid Lymphoma -- 5 Pyothorax-associated lymphoma (PAL) -- 6 Stomach -- 7 Intestinal lymphomas -- 8 Primary Testicular Lymphoma -- 9 Cutaneous Lymphomas.
Keywords: Medicine; Radiotherapy; Hematology; Oncology; Medicine & Public Health; Radiotherapy; Oncology; Hematology